Chapter Measuring the movement between employment and self-employment: a survey proposal - Fabbris, Luigi (Proceedings e report, 2021)
The study concerns the following issues: 1) basic definitions (traditional craftsmanship and commercial work, self-employment, freelance jobs, learned professions, etc.); 2) analysis of the sources on, and the organizations representing the workers of the self-employment compound; 3) medium-to-long term analysis of the main components of the self-employment compound and of the occupation in self-employment companies. We examined various statistical sources on self-employment in Italy, a category including about 5.5 million workers, according to official estimates. We examined the yearly data of the time span from 2009 to 2019, with a concept about 2020, the Covid-19 year. In the examined period, we highlighted a dramatic reduction at employment entry of younger cohorts of less educated people (about one million people), just partly compensated by an increase of new entries of aged and highly educated people. The study concludes with a proposal of a set of questions on self-employment that could be used to adjust the specific part of the questionnaire used by Istat for the survey on the Italian labour forces.